Covid-19—Beyond virology: Potentials for maintaining mental health during lockdown - Munk, Aisha J. L.; Schmidt, Norina M.; Alexander, Nina; Henkel, Katrina; Hennig, Juergen (PloS one, 2020)
The current study aimed to assess prevalence of mental disorders during Covid-19 pandemic- and respective lockdown in Germany, and potential behaviors/states that can have protective functions on preventing severe mental problems. Assessing prevalence of mental disorders, as well as to find potential protective variables is very important in order to determine people's psychological suffering. It provides the basis for teaching possible coping styles in order to prevent a major breakdown on mental health. Prevalence on mental disorders was expected to increase during the pandemic, especially depression, (general-/and health-) anxiety, panic attacks- and disorder, as well as obsessive-compulsive disorder. Additionally, potentially protective variables, such as resilience and coping, were included. N = 949 subjects completed an online-survey that asked for symptoms regarding depression, (health) anxiety, panic disorder, obsessive-compulsive disorder, and lock-down related behavior-starting 14 days after lockdown in Germany. Prevalence of mental disorders in the current sample was much higher than usual prevalence of mental disorders, with 50.6% expressing at least one mental disorder. Resilience was associated with lower risks for any mental disorder (OR = 4.23, p < .0001, 95%CI = 3.21-5.57), as well as with any other measured mental illness (all ORs between = 2.82 for obsessive-compulsive disorder and OR = 41.44 for panic disorder, all p < .001). Similar results were obtained regarding coping (focus on positive). Results are highly relevant in order to provide a glance on what substantial influence the current pandemic- and lockdown situation has on mental health across the country, and possibly across the world. Possible ways in order to prevent deterioration and help coping with the current situation are being elaborated and discussed.